THE MIRROR OF INDONESIAN MARRIAGE ACT (STUDY OF UNREGISTERED DIVORCE IN MALAY SOCIETY IN TANJUNG PURA SUBDISTRICT, LANGKAT) - Fatimah Zuhrah (Pusbindiklat - LIPI, 2011)
The aim of this study is to see the divorce between a couple without court process decision as a crucial issue in Indonesian Marriage Act No. 1/1974. In an article 39 of the Marriage Act No. 1/1974 paragraph (1) mentioned:Divorce can only be done in front of a competence court and through the trial court after the Court tried and failed to reconcile the two sides. Even though Indonesian marriage act had reformed as a unity handbook for all Indonesian people, but in fact, its presence has not been received as positive response in terms of implementation and practice. For the majority of Malay community in the District of Tanjung Pura, the divorce can only be done in front of the judge and through the trial, as stated in article 39 of the Marriage, is relatively large wedge. Many factors causing its objections are: Fiqh oriented, internal judiciary, lack of legal awareness, and many factors related to facilities and infrastructures.